Five feet apart - Lippincott, Rachael; Daughtry, Mikki; Iaconis, Tobias, 1971- (Simon & Schuster Books for Young Readers, 2018)
Seventeen-year-olds Stella and Will, both suffering from cystic fibrosis, realize the only way to stay alive is to stay apart, but their love for each other is slowly pushing the boundaries of physical and emotional safety.